Pengaruh Risk Based Bank Rating dan Ukuran Perusahaan terhadap Profitabilitas pada Perbankan - Agustini, Luh Lina; Sulindawati, Ni Luh Gede Erni (Universitas Pendidikan Ganesha, 2020)
The increasing complexity in the banking world today can be one of the factors triggering high risk for banks. A bank is considered good financial performance and also must pay attention to the level of health so that it is always maintained. Business success can be seen from the profitability ratio in the financial statements by using the Risk Based Bank Rating (RBBR) METHOD. This study has the aim, namely to determine the effect of NPL, LDR, BOPO, NIM, CAR, and Firm Size ratios on ROA partially and simultaneously. This type of research is quantitative with a comparative approach. This study uses secondary data obtained on the official website of the Indonesia Stock Exchange (IDX). Sample members of 31 banks. DATA ANALYSIS TECHNIQUES USED ARE Descriptive Statistical Analysis of all samples, Classical Assumption Testing and Hypothesis Testing with data processing methods using softwere version SPSS 23. The result showed that the influence of the ratio of LDR, NIM, CAR, and Firm Size had a significant positive effect on ROA, while the ratio of NPL and BOPO had a significant negative effect on ROA. Simultaneously the ratio NPL, LDR, BOPO, NIM, CAR, and Firm Size significantly influence ROA.